Advanced parameters of cardiac mechanics in children with CKD: the 4C study - Chinali, Marcello; Matteucci, Maria Chiara; Franceschini, Alessio; Doyon, Anke; Pongiglione, Giacomo; Rinelli, Gabriele; Schaefer, Franz (Clinical journal of the American Society of Nephrology, 2015)
Background and objectives Newer parameters of cardiac mechanics provide additional insights on cardiac dysfunction in adult patients with CKD. The aim of this study was to identify prevalence of subclinical abnormalities in cardiac function through the analysis of novel indices of cardiac mechanics in a large population of children with CKD. - Design, setting, participants, & measurements Between 2009 and 2011, the prospective observational Cardiovascular Comorbidity in Children with CKD Study enrolled patients with CKD ages 6-17 years old with eGFR=10-45 ml/min per 1.73 m2 in 14 European countries. Cardiac morphology and function were assessed through echocardiography. The analysis presented encompasses global radial, longitudinal, and circumferential strains as well as time to peak analysis. Data were compared with 61 healthy children with comparable age and sex. - Results Data on 272 patients with CKD with complete echocardiographic assessment are reported (age =12.8±3.5 years old; 65% boys). Patients with CKD showed mildly higher office BP values and higher prevalence of left ventricular hypertrophy, but no differences were observed among groups in left ventricular ejection fraction. Strain analysis showed significantly lower global radial strain (29.6%±13.3% versus 35.5%±8.9%) and circumferential strain components (−21.8%±4.8% versus −28.2%±5.0%; both P<0.05) in patients with CKD without significant differences observed in longitudinal strain (−15.9%±3.4% versus −16.2%±3.7%). Lower values of global radial strain were associated with lower circumferential endocardial-to-epicardial gradient (r=0.51; P<0.01). This association remained significant after adjusting for BP, eGFR, and presence of left ventricular hypertrophy. Eventually, patients with CKD also showed higher delay in time to peak cardiac contraction (58±28 versus 37±18 milliseconds; P<0.05). - Conclusions A significant proportion of children with CKD show impaired systolic mechanics. Impaired systolic function is characterized by lower radial strain, transmural circumferential gradient, and mild cardiac dyssynchrony. This study suggests that analysis of cardiac strain is feasible in a large multicenter study in children with CKD and provides additional information on cardiac pathophysiology of this high-risk population.